2017
DOI: 10.1515/jpem-2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic and clinical delineation of 22 patients with congenital hypogonadotropic hypogonadism

Abstract: The frequency of CHH genes in the Japanese was compatible with previous reports, except that CHD7 mutations might be more common. Furthermore, partial phenotype-genotype correlations were demonstrated in our cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…15 AR AURKC CATSPER1 CCDC39 CFTR CHD7 DNAAF1 DNAAF2 DNAAF3 DNAH1 DNAH11 DNAH5 DNAI1 DNAI2 DPY19L2 DYX1C1 ETV5 FGF8 FGFR1 GNRHR HEATR2 HSF2 HYDIN KAL1 KISS1R LEP LEPR NANOS1 NELF NR5A1 PLCZ1 PROK2 PROKR2 RHOXF1 RHOXF2 RSPH1 RSPH4A RSPH9 SEPT12 SLC26A8 SOHLH2 SPATA16 SUN5 SYCE1 SYCP3 TAC3 TACR3 TEX11 USP26 WDR11 ZMYDN15 In previous studies, KISS1R was one of the major genes that implicated in IHH in the autosomal-recessive form. 16 Mutations of this gene have been identified in less than 5% of patients with normosmic IHH. 12 Up to now, at least 20 different mutations have been described in the literature, most of which were loss-of-function mutations and were found to have variable clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…15 AR AURKC CATSPER1 CCDC39 CFTR CHD7 DNAAF1 DNAAF2 DNAAF3 DNAH1 DNAH11 DNAH5 DNAI1 DNAI2 DPY19L2 DYX1C1 ETV5 FGF8 FGFR1 GNRHR HEATR2 HSF2 HYDIN KAL1 KISS1R LEP LEPR NANOS1 NELF NR5A1 PLCZ1 PROK2 PROKR2 RHOXF1 RHOXF2 RSPH1 RSPH4A RSPH9 SEPT12 SLC26A8 SOHLH2 SPATA16 SUN5 SYCE1 SYCP3 TAC3 TACR3 TEX11 USP26 WDR11 ZMYDN15 In previous studies, KISS1R was one of the major genes that implicated in IHH in the autosomal-recessive form. 16 Mutations of this gene have been identified in less than 5% of patients with normosmic IHH. 12 Up to now, at least 20 different mutations have been described in the literature, most of which were loss-of-function mutations and were found to have variable clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also reported that both dominant and recessive forms of CHH transmission were present in patients with TACR3 mutations and patients with heterozygous mutations were clinically similar to those with homozygous mutations . But most researches suggested that TACR3 was autosomal recessive inheritance, offsprings with heterozygous mutations were not affected …”
Section: Discussionmentioning
confidence: 99%
“…12 But most researches suggested that TACR3 was autosomal recessive inheritance, offsprings with heterozygous mutations were not affected. 13,17,18,21,25 The pathogenicity of the variant may be due to the dominant negative effect. Noel et al reported the mechanisms of another heterozygous mutation in TACR3 disrupting NK3R function in GnRH-deficient patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consented gene list that should be offered for patients providing an accurate diagnosis for the majority of cases. After publication of the expert consensus 7 CHH gene panel testing studies were reported (Table 2) (Quaynor et al 2016;Aoyama et al 2017;Wang et al 2017;Cassatella et al 2018;Zhou et al 2018;Amato et al 2019;Kim et al 2019). In these studies, 25-261 genes were included as susceptibility genes of CHH.…”
Section: Testing Strategiesmentioning
confidence: 99%
“…Regarding phenotype-genotype correlation some authors reported inconclusive results and little co-segregation by analyzing pedigrees in their cohorts (Aoyama et al 2017;Zhou et al 2018), probably due to the complex genetic background of CHH. However, differences in genetic profile among populations are indicated in Chinese and Japanese cohorts (Aoyama et al 2017;Zhou et al 2018). Zhou et al reported that in Chinese population, cryptorchidism was the most common accompanying feature in addition to CHH, but no single gene in their panel showed association with this abnormality (Zhou et al 2018).…”
Section: Pathogenicity Of the Identified Variants Genotypephenotype mentioning
confidence: 99%